The Effectiveness of Positive Cognitive Behavioral Therapy on the Positive and Negative Affect of women with spouse with Mental Disorders - a gh; faezeh komeylipour (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2019)
The aim of this study was to determine the effectiveness of positive cognitive-behavioral therapy on female's positive and negative affection with spouse with mental disorders in Isfahan city. The research method was a quasi-experimental design with pre-test-post-test design with control group. The statistical population included all women with spouse with mental disorder referred to counseling centers under the welfare organization of Isfahan. The sampling method was purposeful and among 30 women who were willing to cooperate in therapeutic sessions, they were assigned randomly in two groups: experimental (15) and control group (15). The experimental group received 10 sessions of positive cognitive behavioral therapy. After completion of sessions and 45 days after the follow up, they responded to the Watson et al. (1988) positive and negative affective questionnaire. The results of multivariate analysis of covariance showed that positive cognitive-behavioral therapy interventions increased positive emotional and decreased negative affect in the experimental group compared to the control group (p <0.001). In addition, this effect has been confirmed in the follow-up phase (p <0.001). Therefore, positive cognitive-behavioral interventions can be used to increase positive affection and reduce negative affection for women with spouse with mental disorders.